Intégration d’un PVS sur les réseaux électriques - Gueniaa, bilal; Bourouba, abdelkrim; Ahmouda, miloud; Ahmed, Matouh (université d'eloued, 2023)
" Given the widespread number of users from the mains and also the increase in network load, the electricity distribution companies attempt to provide the energy required by good design and operation of the network .With regard to the widespread use of distributed generation in the distribution network , technical impacts in the distribution system must be carefully analyzed. In this memoir, decentralized production is placed optimally at the radial distribution network and for different load levels , with the aim to reduce the total loss of active power. And the effect of decentralized production on improving the voltage profile has been considered in this memoir. An optimization algorithm known algorithm BAT is used to find optimal solutions. The performance of the proposed algorithm is evaluated on an IEEE 33 distribution network." "نظرا لازدياد الطلب على الطاقة الكهربائية وكذلك الزيادة في حمولة الشبكة، تسعى شركات توزيع الطاقة الكهربائية لتوفير الطاقة الكافية لسد جميع الاحتياجات وذلك التشجيع على الانتاج اللامركزي لهذ الطاقة. كما يجب تحليل آثارها الفنية في شبكة التوزيع بعناية. في هذه المذكرة، يتم دمج الانتاج اللامركزي للطاقة الكهربائية بشكل مثالي على مستوى شبكة التوزيع شعاعية ومن اجل مستويات مختلفة للحمل، بهدف التقليل من نسبة الضياعات النشطة وكذلك تحسين التوتر الكهربائي يجب تحديد المكان الامثل لتثبيت هذ المصادر. في هذه المذكرة تم استخدام خوارزمية معروفة اسم خوارزمية الخفاش من اجل تحديد الحلول المثلى. تم تقييم اداء الخوارزمية المقترحة على شبكة توزيع معيارية 33عقدة. "
مذكرة ماستر الكتروميكانيكdes thèses électromécanique
Keywords: Distribution network, decentralized production, Bat algorithm.; شبكة التوزيع، التوزيع اللامركزي، خوارزمية الخفاش